Assessing the incidence of tongue coating in patients treated in intensive care units - Alexandre Franco Miranda; Giovanna Louly Caixe El Haje; Renata Monteiro de Paula; Priscila Paganini Costa; Maria Gabriela Haye Biazevic (Associação Brasileira de Odontologia, 2018)
Objective: assessing the incidence of tongue coating in patients treated in the intensive care unit (ICU) of a hospital in Federal District, Brazil. Material and Methods: descriptive and prospective study with convenience cohort approved by the Research Ethics Committee. A single examiner conducted clinical examinations focused on evaluating the incidence of tongue coating in ICU patients for 5 weeks, at times scheduled by the ICU management board. Data were recorded in a standardized datasheet. Results: we assessed 152 male and female patients (57% women and 42% men), at mean age 64 years. Patients were hospitalized in the ICU, mostly under normal conditions (p < 0.001); the longest period in the ICU was 48 hours (p < 0.001). Most patients (56) presented coating throughout their tongues (p